An operating parameter study of the biomass solid feedstock incinerator of fixed-bed type with two stage air supply. Issue 1 (1st February 2022) - Simanjuntak, J P; Daryanto, E; Tambunan, B H; Eswanto,
Abstract: Due to the lack of the instrument, a biomass incinerator operating parameter can be studied through the stack gas for a preliminary to the incinerator operating parameters design and development. The main objective of this paper is to derive the equations which can be used to predict the air required to reach complete combustion through the stack gas analysis. Molecular mass of the biomass was determined based on the stack gas composition which was measured by means of hand-held gas detector. The ratio of the air flow rate supplied to the biomass rate is considered and monitored as well as the flame temperature of the stack gas at the outlet. By adjusting the air flow rate into the primary and secondary combustion zones, a stable and complete combustion was possibly reached. High stack gases temperature, percentage of oxygen or carbon dioxide by volume of the stack gases then were used as the criteria to the optimum operating parameters required. This method is helpful to the incinerator optimization with lack of instrument, since it is thought that the incinerator may meet domestic emission limits with good combustion control through proper and precise operation.